HUBUNGAN PENDAPATAN KELUARGA TERHADAP KEJADIAN BAWAH GARIS MERAH (BGM) PADA BALITA USIA 0-5 TAHUN : THE RELATIONSHIP BETWEEN FAMILY INCOME TO THE INCIDENCE OF UNDER RED LINE WEIGHT IN TODDLERS AGED 0-5 YEARS - Gilang akbar shobirin; Diah Pitaloka Putri; Puspita, Enny (LPPM STIKes Bahrul Ulum Jombang, 2023)
Introduction: The incidence of Below the Red Line (BGM) is a growth disorder that occurs in toddlers where the results of weight measurements are below of red line on the KMS. Risk factors that cause of below the red line are family income, maternal knowledge, birth interval Objective: to determine the relationship between family income and the incidence of Under the Red Line (BGM) for toddlers aged 0-5 years. Methods: This study was conducted in April 2023 in Public Health of Karangkembang Babat with a cross sectional design. The independent variables were family income variable and the incidence of Below the Red Line (BGM) as the dependent variable. The number of research samples was 50 toddlers aged 0-59 months with sampling using total sampling. Statistical analysis using rank spearman correlation. Results: There is a relationship between family income and the incidence of Below the Red Line (BGM) in toddlers 0-5 years (p value = 0.000). Conclusion: Family income will affect the incidence of Below the Red Line (BGM). Higher income will increase the family's food. Suggestion: families of toddlers to be able to increase the amount of food provision, especially for toddlers to improve nutritional status.